Development and evaluation of an ACT-based lifestyle education intervention for patients with pre-diabetes : a randomised controlled trial : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Malthus, Sarah (Massey University, 2019)
Type 2 diabetes is a potentially debilitating health condition, and rising prevalence rates of both diabetes and pre-diabetes (the precursor to diabetes) globally and in New Zealand has made prevention an important research focus. Early research indicated dramatic reductions in modifiable diabetes risks factors through the provision of lifestyle education interventions for those with pre-diabetes. However, the time and resource intensive nature of these interventions presented challenges for their implementation, and studies employing briefer more pragmatic interventions produced less compelling results. Incorporating a psychological component into lifestyle education interventions has been highlighted as a possible avenue for enhancing outcomes. This thesis describes the development/adaptation of two intervention approaches for patients with pre-diabetes; lifestyle education alone and lifestyle education combined with Acceptance and Commitment Therapy (ACT). The goal of the ACT/Education approach was to connect participants’ lifestyle goals to personally meaningful values, and equip them with skills to deal with difficult emotions that can function as barriers to goal attainment. A randomised controlled design was used to compare the effectiveness of these approaches with the provision of standard medical care. Results indicated the presence of significant cumulative intervention effects over time for HbA1c, BMI, waist circumference, saturated fat intake, life satisfaction, anxiety, and pre-diabetes knowledge; and education alone was more effective than standard care for reducing total cholesterol and waist circumference. However, results indicated that incorporating an ACT approach was no more beneficial than education alone or standard care across any of the outcome measures. Limitations related to statistical power, participant characteristics and methodology makes definitive interpretations of these results difficult. Addressing these limitations in future research may produce more meaningful outcomes.
Keywords: Prediabetic state; Treatment; New Zealand; Non-insulin-dependent diabetes; Prevention; Acceptance and commitment therapy; 520304 Health psychology